2020
DOI: 10.1002/jsfa.10821
|View full text |Cite
|
Sign up to set email alerts
|

A brief hot‐water treatment alleviates chilling injury symptoms in fresh tomatoes

Abstract: BACKGROUND Reducing the negative effects of chilling injury (CI) in tomatoes after harvest is essential to ensure good quality and to minimize losses. CI is a postharvest disorder associated with the generation of reactive oxygen species (ROS) in the fruit. Therefore, antioxidant accumulation can counteract ROS, alleviating CI symptoms. In this sense, it has been confirmed that a brief hot‐water (HW) immersion promotes the synthesis of antioxidants. RESULTS HW treatment at 52 °C for 5 min significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 60 publications
(70 reference statements)
0
6
0
1
Order By: Relevance
“…However, when the cold storage temperature is lower than 6°C, CI will occur (Hashim et al, 2013). Presently, there are many inhibiting banana CI methods including heat treatment, cold shock treatment, UV, ultrasonic wave, low temperature plasma, and biochemical preservatives (Jinglin et al, 2020; Khademi, Ashtari, & Razavi, 2019; Loayza et al, 2020; Sun, Chen, Kuang, Chen, & Lu, 2010; Zhou, Pan, Qu, & Underhill, 2014; Zhou, Sun, Li, Zhu, & Tu, 2019). Food electromagnetic field processing technology is a new treatment method with rapid development in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the cold storage temperature is lower than 6°C, CI will occur (Hashim et al, 2013). Presently, there are many inhibiting banana CI methods including heat treatment, cold shock treatment, UV, ultrasonic wave, low temperature plasma, and biochemical preservatives (Jinglin et al, 2020; Khademi, Ashtari, & Razavi, 2019; Loayza et al, 2020; Sun, Chen, Kuang, Chen, & Lu, 2010; Zhou, Pan, Qu, & Underhill, 2014; Zhou, Sun, Li, Zhu, & Tu, 2019). Food electromagnetic field processing technology is a new treatment method with rapid development in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…(1 week at 12.5°C) showed an increase in phenolics after the fruits were ripened, but the opposite was observed when the tomatoes were stored for 1 week at 5°C (Loayza et al, 2021). HWT did not affect the phenolics content in mature green fruit at any of the evaluated conditions; furthermore, there were no significant differences in the antioxidant activities measured by the ORAC and FRAP methods (Loayza et al, 2021).…”
Section: Chilling Injury Tolerance In Hot Water-treated Tomatoes Is Associated With Increased Phenolics Content and Antioxidant Activitymentioning
confidence: 85%
“…Imperial) has been associated with changes in the expression of genes encoding heat shock proteins and enzymes of the antioxidant system and the energy metabolism (Cruz-Mendivil et al, 2015;Salazar-Salas et al, 2017); however, the metabolites associated with such tolerance have not been identified. In this regard, the CI tolerance induction has been associated with a range of metabolites and depends on the species, varieties of the same species, and developmental stage, among other factors (Aghdam et al, 2019;Albornoz et al, 2019;Datir et al, 2020;Gonzalez et al, 2019;Jannatizadeh et al, 2019;Loayza et al, 2021;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This treatment preserved the quality of the peppers, inhibited phenylalanine ammonia lyase (PAL) activity, and did not markedly affect the peppers' antioxidant content during storage [30]. Immersing breaker-turning tomatoes into water at 52 • C for 5 min significantly increased (by 17%) their lycopene content after 2 weeks of storage at 5 • C. This treatment also increased the tomatoes' ascorbic acid content by 11%, their lipophilic phenolic content by 18%, and their total phenolic content by 6.5% [31]. In another study, mature-green tomatoes were immersed in hot water (52 • C) for 5 min [32].…”
Section: Physical Treatments and Phytochemicalsmentioning
confidence: 99%